(untitled) (Research, Society and Development, 2021)
COVID-19 is a contagious disease, of immeasurable proportions, caused by SARS-CoV-2 (new coronavirus). Due to this scenario, we are facing a great challenge, for which we still don’t have all the answers. This study aimed to investigate the influence of the pandemic on quality of life and its relationship with the permanence of students enrolled in the Psychology course at campus AC Simões, Federal University of Alagoas. This is a quantitative research, obtained with the application of the Likert-type scale instrument added by a situational and sociodemographic inventory and the assessment of quality of life through the WHOQOL-bref tool. Based on the research results, it was possible to reflect a feeling of being more or less covered by the various consequences on quality of life and the significant impacts in this process, especially in the way we will live and work. Dialogue on care practices and new procedures for the functioning of classes, learning and administrative components will be endowed with virtuality in place of face-to-face support. The results suggest that the pandemic situation can be considered a determinant that affects different dimensions of students’ lives and, in view of such changes, digital transformations will come to play a leading role in life inside and outside universities.